ANALISIS TREN CHILDFREE TERHADAP KEBERLANGSUNGAN BONUS DEMOGRAFI DI INDONESIA - Mubarokah, Elisya Ahsanal; Salsabil, Adynda Putri; Hidayatullah, Agus Efendi; Hartanto, Dhimas Rudy (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2025)
The childfree phenomenon, which refers to the conscious decision not to have children, is gaining attention among Indonesia's younger generation. This trend emerges as part of broader social changes, including individual freedom, gender equality, and the role of social media in shaping worldviews. Indonesia, which is projected to reach its demographic dividend peak during the 2030-2040 period, faces potential impacts from this trend on the sustainability of its demographic dividend. Although this phenomenon has not yet become dominant, it could lead to a decline in birth rates and risk accelerating the aging process of the population. The decline in birth rates caused by this trend could threaten the sustainability of Indonesia's demographic structure, which heavily relies on the working-age population to maintain economic growth.This study aims to analyze the impact of the childfree trend on the sustainability of Indonesia's demographic dividend. It also explores whether the influence of Western culture promoting individualism is more dominant than domestic socio-economic factors in influencing the decision to choose a childfree lifestyle. Additionally, this study examines the role of social media in disseminating the childfree discourse. Using a qualitative approach through in-depth interviews with sociologists, this study is expected to provide insights into the social and economic factors underlying this trend, as well as its implications for Indonesia's demographic policies. The findings of this study are expected to contribute significantly to the formulation of policies that balance individual reproductive rights with the demographic needs of the country to avoid threats to national economic growth. Â Â